P041 Tissue gene profiling uncovers cadherin 11 related signatures in rheumatoid arthritis patients. (21st February 2018) - Hatje, K; Kam-Thong, T; Hartl, D; Duchateau-Nguyen, G
Abstract : Introduction: Cadherin 11 is selectively expressed by synovial fibroblasts and plays a role in the pathogenesis of rheumatoid arthritis (RA). 1 Consequently, blocking cadherin 11 function in inflamed tissues may represent a potentially effective and novel therapy for RA. Objectives: Here we interrogated publicly available transcriptomics datasets from RA patients synovial tissue and healthy controls using pre-defined primary cell gene signatures to better understand the heterogeneity of the underlying pathology. In addition, we analysed the association of these gene signatures with the expression of cadherin 11 gene to narrow down the underlying mechanistic network on which targeted treatments and biomarkers can be developed. Methods: We used two publicly available transcriptomics studies from NCBI Gene Expression Omnibus 2 performed on synovial tissue of RA patients and healthy controls: GSE7307 (RA=5, healthy=7) and GSE77298 (RA=16, healthy=7). The pre-defined gene signatures were derived from ENCODE primary cell expression data 3 and signature enrichment was applied using the BioQC package. 4 Principal component analysis (PCA) was applied on the BioQC enrichment scores to (i) identify potential clusters of samples and to (ii) identify the gene signatures responsible for the clustering. In addition, associations between cadherin 11 gene expression and gene signatures were tested. Results: In both studies, cadherin 11 was higher expressed in RA patients compared to healthy controls. PCA performed on gene enrichment scores showed RA patients clustered apart from the healthy controls. Moreover, fibroblast, macrophage, lymphocyte and osteoclast gene signatures were significantly enriched in the RA patients compared to healthy controls in both studies. Unexpectedly, an adipokine-related signature was significantly enriched in RA patients from one transcriptomics dataset (GSE77298), while only showing a trend in the second set (GSE7037). In addition, in both studies Cadherin 11 was associated positively with fibroblast and lymphocyte signatures and negatively with adipokines-related signature. Conclusions: The identified cadherin 11 related gene signatures expand our knowledge on cadherin 11 biology in human RA and may serve as potential biomarkers for RA studies in the future. References: . Lee, et al. Science 2007;315:1006–10. . https://www.ncbi.nlm.nih.gov/geo/ . ENCODE Project Consortium. Nature2012;489(7414):57–74. . Zhang, et al. BMC Genomics2017;18(1):277. Disclosure of interest: K. Hatje Employee of: Roche, T. Kam-Thong Employee of: Roche, D. Hartl Employee of: Roche, G. Duchateau-Nguyen Employee of: Roche